CONSUMERS INTENTION TO BUY BRANDED FRESH LEAFY VEGETABLES AMONG RURAL AND URBAN HOUSEHOLDS - Moradeyo Adebanjo OTITOJU (Slovak University of Agriculture, 2021)
Research background: The intention of consumers to purchase branded goods and services is a building block for purchasing behaviour in agribusiness especially for fresh leafy vegetables with nutritional and health benefits in Africa. Purpose of the article: To examine the determinants of consumers’ intention to purchase fresh leafy vegetables, and to identify the constraints militating against shopping outlet decisions of fresh leafy vegetables by the rural and urban households in the Federal Capital Territory, Nigeria. Methods: The sampling techniques were employed to collect data from primary source were stratified, purposive and convenience to select 746 respondents (396 of urban and 350 of rural households). But 608 respondents (294 for Urban area and 314 for rural area, which represents 74.2% and 89.7%, respectively) were later used for the analysis. Convenience sampling was used at a point because there is no reliable sampling frame that was existing for the respective places. Findings & Value: This study reveals that are household size, farming as a primary occupation and distance of the consumers’ residence to the point of purchase leafy vegetables among both rural and urban households, with the exception of personal income which only influenced the purchasing intention of urban consumers. Poor storage facilities for fresh leafy vegetables was a major constraint to both rural and urban households in the choice of shopping outlets for fresh leafy vegetables in the Federal Capital Territory, Nigeria. All-inclusive policies should be enacted that has the potential to enhance the storage facilities for fresh leafy vegetables. For branded leafy vegetables to be purchased the shopping outlets must be made closer to the residence of the consumers.